Все элементарно просто а) 3,4x+ 5,7x+6,6x-4,7x=(3,4+5,7+6,6-4,7)x=11х Если х=3,6, то выражение 11х=11*3,6=9,6 Если х=0,8, то выражение 11х=11*0,8=8,8 Если х=10, то выражение 11х=11*10=110
б) 3,8m-(2,8m+0,7m)=3,8m-2,8m-0,7m=(3,8-2,8-0,7)m=0,3m Если m=2,4, то выражение 0,3m=0,3*2,4=0,72 Если m=8,57, то выражение 0,3m=0,3*8,57=2,571
в) 16,75y-(4,75y+10,8)=16,75y-4,75y-10,8=(16,75-4,75)y-10,8=12y-10,8 Если у=0,9, то выражение 12y-10,8=12*0,9-10,8=10,8-10,8=0 Если у=3,01, то выражение 12y-10,8=12*3,01-10,8=36,12-10,8=25,32
Все элементарно просто а) 3,4x+ 5,7x+6,6x-4,7x=(3,4+5,7+6,6-4,7)x=11х Если х=3,6, то выражение 11х=11*3,6=9,6 Если х=0,8, то выражение 11х=11*0,8=8,8 Если х=10, то выражение 11х=11*10=110
б) 3,8m-(2,8m+0,7m)=3,8m-2,8m-0,7m=(3,8-2,8-0,7)m=0,3m Если m=2,4, то выражение 0,3m=0,3*2,4=0,72 Если m=8,57, то выражение 0,3m=0,3*8,57=2,571
в) 16,75y-(4,75y+10,8)=16,75y-4,75y-10,8=(16,75-4,75)y-10,8=12y-10,8 Если у=0,9, то выражение 12y-10,8=12*0,9-10,8=10,8-10,8=0 Если у=3,01, то выражение 12y-10,8=12*3,01-10,8=36,12-10,8=25,32
2. 176+100 = 276
2) (684+915)-484
1. 684-484 = 200
2. 200+915 = 1115
3) (259+101)-59
1. 259-59 = 200
2. 200+101 = 301
4) 1287-(487+164)
1. 1287-487 = 800
2. 800-164 = 636
5) 971-(235+371)
1. 971-371 = 600
2. 600-235 = 365
6) 5393-(1393+158)
1. 5393=1393 = 4000
2. 4000-158 = 3842